PERBANDINGAN KEMAMPUAN MENGONVERSI TEKS LAPORAN HASIL OBSERVASI KE DALAM PUISI MENGGUNAKAN MODEL DISCOVERY LEARNING DAN MODEL PEMBELAJARAN LANGSUNG - Rini Kartini Saputri; Abdoel Gafar; Firman Tara (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research is intended to identify the students ability in converting report text to a poetry that was taught by using discovery learning. This research is quantitative with quasi experimental design. The population of this research is students of class X MIPA SMA Negeri 10 Kota Jambi. In collecting sample, random sampling is used, in which class X MIPA1 is experiment class and class X MIPA 2 is a control class. The technique of collecting the data is test. The data is analyzed by using pretest analysis, normality test, homogeneity test, and hypothesis test. The result of the research shows that the mean score of experiment class is 75,00 and the mean score of control class is 71,80. The hypothesis test is calculated by using SPSS 20. T-test of two samples is gained with t-count 0,049 < 0,05 in which Ho is rejected and Ha is accepted. Based on the result of the analysis, it can be concluded that students ability in converting report text into poetry can be taught by using discovery learning compared with those students who tried to convert the report text into poetry with direct learning model.Key Words: report text, poetry, discovery learning